Look before you leap (A) : considering a job offer with an early-stage company - Rogers, Steve (SAGE Knowledge. Cases., 2017)
In the fall of 2007 a senior director of product marketing at Qwest in Denver, Colorado, gets an offer to work for an entrepreneurial high-growth venture. The vision is for greater wealth, accelerated business opportunity, more thrill on the job, and faster path to leadership by pursuing a position with a start-up firm. Kiva Allgood has management responsibility in her current position (e.g., manages a high-budget portfolio), with compensation of $145,000 in salary and incentive bonuses up to 100% of base salary. She realizes that she is not prepared for the negotiation because she has only negotiated job offers within large firms. She needs to know what many of these entrepreneurial finance terms mean and to understand whether she is being offered terms and amounts commensurate with the value she feels she will bring to the entrepreneur. She also needs to understand her opportunity cost and the expected value of her options: staying with the current job, starting her own venture, or taking this offer at the entrepreneurial venture. She had no idea there were also so many additional, non-financial factors to take into consideration. With her future on the line, she needs to work through the numbers fast. The entrepreneur gave her five days to come back with a counter offer, which he considered a generous amount of time. In evaluating these questions, students will take Allgoods point of view. The case is based on a real job offer to a real person named Kiva Allgood. The entrepreneur and his firm are fictitious in order to heighten the issues in this situation.